Application of Fucoxanthin Pigment Extract from Sargassum sp. on the Physical Quality of Blusher Preparation - Dessy Nuraini; Moch. Amin Alamsjah; Eka Saputra (Journal of Marine and Coastal Science)
Sargassum sp. is a brown algae (Phaeophyta) which contains fucoxanthin, i.e. a carotenoid pigment that can be developed as natural dyes. On the cheek coloring products (blusher), color is an important parameter that determines the consumer appeal. This study was carried out by extraction, purification, qualitative and quantitative analysis, making blusher preparation with addition of fucoxanthin pigment extract form Sargassum sp. of 4%, 5%, 6% and 7%, physical quality and antioxidant activity test in the best treatment. The results of this study indicated the application of fucoxanthin pigment extract from Sargassum sp. giving effect to the physical quality of blusher. This blusher preparation had good color homogeneity and almost the same particle size as the commercial blusher. It also had good color stability during 15 days of storage with a change in pH which increases between 8,32-9,34. The irritation reaction that occurred on 10 panelists were undetected and it had the highest hedonic value on blusher with the addition of 4% fucoxanthin. The best treatment in this study was blusher with 4% addition of fucoxanthin pigment extract. The 4% treatment had good homogeneity and color stability. The skin irritation was undetected, it had the most neutral pH value or matches with physiological pH value of the skin and had a moderate antioxidant activity with an IC50 value of 123,66 Î¼g/mL and blusher had a shape like small chunks with a mean size of 36,79 Î¼m in SEM analysis.